2014
DOI: 10.1016/j.sbspro.2014.11.160
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Graphs in Malaysian Companies’ Corporate Reports: A Longitudinal Study

Abstract: The purpose of this paper is to examine the nature and extent of voluntary disclosure of graphical information in the annual reports of 54 non-financial public listed companies in Malaysia using a longitudinal approach. The results show that the disclosure of graphical information in Malaysian companies' annual reports has increased at an 'average level' over the thirtyyear period. The majority of Malaysian companies prefer to use the bar graphs and the most frequently graphed variables are profit, turnover, e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 43 publications
1
5
0
Order By: Relevance
“…For instance, Beattie et al (2008) conducted a cross-case comparison of graph use in the UK companies from the 1960s through to the early 2000s and found that more graphs were used and that a larger share of companies used at least one graph by 2004. A study of Malaysian firms found similar patterns of increasing graph use over time (Abdul Rahman et al, 2014). As with several related studies (McKinstry, 1996;Bartlett and Jones, 1997;David, 2001;Ditlevsen, 2012b), Beattie et al (2008) also found that the annual reports had become longer.…”
Section: Related Studiessupporting
confidence: 62%
See 1 more Smart Citation
“…For instance, Beattie et al (2008) conducted a cross-case comparison of graph use in the UK companies from the 1960s through to the early 2000s and found that more graphs were used and that a larger share of companies used at least one graph by 2004. A study of Malaysian firms found similar patterns of increasing graph use over time (Abdul Rahman et al, 2014). As with several related studies (McKinstry, 1996;Bartlett and Jones, 1997;David, 2001;Ditlevsen, 2012b), Beattie et al (2008) also found that the annual reports had become longer.…”
Section: Related Studiessupporting
confidence: 62%
“…The trend of increasing frequency of visuals use in annual reports has inspired many studies to date. These studies frequently focus on photographs (Davison, 2015), and have shown that photographs can be used to portray key actors within the company, such as CEOs (Davison, 2010), employees (Anderson and Imperia, 1992), and customers (Dougherty and Kunda, 1990). Similarly, Campbell et al (2009) explored the morality of representing faces in corporate communication.…”
Section: Related Studiesmentioning
confidence: 99%
“…Research has investigated the change and structure in the annual integrated report and results indicate that the size and proportion of voluntary information have increased and there has been a change in the use of alternate communication methods, such as graphs and pictures (Bartlett & Jones 1997;Beattie, Dhanani & Jones 2008b;Lee 1994). Companies are no longer focusing on the annual integrated report as being a statutory-driven document but rather as a design-orientated document, which functions as a public relations tool (Beattie et al 2008b;Rahman, Hamdan & Ibrahim 2014). The reasons companies use graphs in the annual integrated reports is discussed in the following section.…”
Section: Change In Reporting Landscape -South Africa and Abroadmentioning
confidence: 99%
“…The author examined the use of graphs and charts in the reports, as well as the graphical distortions in them, via the presence of KFVs and the distortion index, finding evidence of impression management. Rahman et al (2014) proposed establishing the nature and extent of the voluntary disclosure of graphical information in Malaysia in a 30-year period with 10-year intervals (1974, 1984, 1994 and 2004). Most of the companies prefer to use bar charts and there was considerable growth in the amount used over the course of the period.…”
Section: Graphs and Charts Impression Management And Financial Perfomentioning
confidence: 99%
“…It is also suggested that distortions of the graph's physical dimensions, another aspect of graphic infidelity, should be investigated for the sample of this research, duly adjusted to the time horizon. Another possibility would be to investigate the differences between the use of graphics in reports of a market such as Brazil's, where there is still no specific regulation on the issue, and the use of such resources in countries which already have guidelines for the elaboration and dissemination of graphic information (Rahman et al, 2014).…”
Section: Final Remarksmentioning
confidence: 99%